193 13 SECONDS OF ASYSTOLE IN YOUNG: IS A PACEMAKER NECESSARY?. (15th December 2022) - Petrungaro, Mattia; Berton, Giampaolo; Scarà, Antonio; Borrelli, Alessio; Latorre, Maria; Ruvo, Ermenegildo De; Sciarra, Luigi; Calò, Leonardo
Abstract: Introduction: Cardioinhibitory neurocardiogenic syncope (CNS) is caused by inappropriately trigger-activated cardiac reflex which finally precipitates asystole, sinus bradycardia, or atrioventricular block. In the absence of structural heart disease, the prognosis is excellent, but frequent syncopal episodes can have a significant impact on quality of life. No medical therapy has proved to be really effective and studies concerning pacemaker implantation are often controversial. However, in young individuals, especially those under 40 years of age, implanting a pacemaker may carry more risks than benefits. Thus, alternative techniques such as ablation of the cardiac atrial parasympathetic ganglia (GP) have emerged. Case report: A 34-year-old man with frequent episodes of reflex syncope performed a tilt test in March 2022 that diagnosed cardio-inhibitory syncope with 13-second asystole interrupted with external cardiac massage and intravenous atropine. In May 2022 he had an MRI scan showing normal biventricular systolic function and absence of late-gadolinium enhancement and underwent loop recorder implantation. He came to our centre in June 2022 and underwent electrophysiological study and electroanatomical mapping of the right atrium (Carto 3) during general anaesthesia. The anatomical areas of the supero-posterior and infero-posterior GPs of the right atrium were identified by electroanatomical mapping of complex fractionated atrial electrograms (CFAE). Radiofrequency pulses (Thermocool 30 watts) were delivered at these points, resulting in the disappearance of the CFAEs and an increase in basal heart rate. The greatest number of ganglia are allocated on the posterior surface of the right atrium and in particular the supero-posterior GP is the nexus point for vagal input to the GPs before innervating the atria. Therefore, it was decided to localise and ablate exclusively the GPs of the right atrium. The procedure was completed without complications. The patient has not complained of any syncopal episodes since, and the loop has not recorded any significant pauses. Conclusions: The anatomic ablation of GP only in the right atrium could represent a feasible method to reduce CNS, to increase the warning symptoms period, and to delay as much as possible pacemaker implant, especially in young patients who have experienced a related physical trauma. This approach significantly decreased the procedural time and risks.